Santiago - Márquez, Francisca (Urbani izziv, 2011)
This paper discusses research carried out in Santiago, Chile, and addresses the origin and construction of urban identities in this segregated city of thetwenty first century. Based on sociological and ethnographic evidence, urban identity building processes are analysed by observing the occupation, use and appropriation of territory. The hypothesis is that, despite evidence of segregation, modernisation and globalisation, urban people reinvent lifestyles within their territories in order to harmonise their bonds of affection and belonging by using distinguishing markings or "brands" and by adopting typical everyday habits. The modern, segregated and global city is filled with "islands" that convey imagery and desires for a friendlier urban life. This paper analyses areas with community identities, neo community identities and border identities. It suggests that, just as community identities shelter nostalgia for a lost community (by finding refuge or reinventing ways to make the fringes of the city habitable in the background or on the "other side" of the Mapocho River and very near the historical centre of the city), border identities have also arisen and persisted; these subvert the orderly and hegemonic city, resulting in a diverse, heterogeneous and multicultural lifestyle. The result is a synthesis and an urban lifestyle.
Keywords: Čile; diferenciacija; Santiago; segregacija; urbana sociologija; urbani prostor